Differential Signaling and Sugar Exchanges in Response to Avirulent Pathogen- and Symbiont-Derived Molecules in Tobacco Cells - Pfister, Carole; Bourque, Stéphane; Chatagnier, Odile; Chiltz, Annick; Fromentin, Jérôme; Van Tuinen, Diederik; Wipf, Daniel; Leborgne-Castel, Nathalie (Frontiers in Microbiology, 2017)
Plants interact with microbes whose ultimate aim is to exploit plant carbohydrates for their reproduction. Plant-microbe interactions (PMIs) are classified according to the nature of their trophic exchanges: while mutualistic microbes trade nutrients with plants, pathogens unilaterally divert carbohydrates. The early responses following microbe recognition and the subsequent control of plant sugar distribution are still poorly understood. To further decipher PMI functionality, we used tobacco cells treated with microbial molecules mimicking pathogenic or mutualistic PMIs, namely cryptogein, a defense elicitor, and chitotetrasaccharide (CO4), which is secreted by mycorrhizal fungi. CO4 was perceived by tobacco cells and triggered widespread transient signaling components such as a sharp cytosolic Ca2+ elevation, NtrbohD-dependent H2O2 production, and MAP kinase activation. These CO4-induced events differed from those induced by cryptogein, i.e. sustained events leading to cell death. Furthermore, cryptogein treatment inhibited glucose and sucrose uptake but not fructose uptake, and promoted the expression of NtSUT and NtSWEET sugar transporters, whereas CO4 had no effect on sugar uptake and only a slight effect on NtSWEET2B expression. Our results suggest that microbial molecules induce different signaling responses that reflect microbial lifestyle and the subsequent outcome of the interaction.